Exosomal PD-L1 detection in cancer predictive biomarker for response to immune checkpoint blockade therapy - Kansha, Tetsuichi; Ma, Xiaojuan; Wang, Hao; Yu, Xiaotong; Song, Ying; Guo, Zhengyang; Song, Jiagui; Xue, Lixiang; Yang, Jianling (Frontiers in Immunology, 2025)
Programmed death-ligand 1 (PD-L1) carried by tumor-derived exosomes has emerged as a critical mediator of immune evasion and resistance to immune checkpoint blockade therapy. Unlike membrane-bound PD-L1, exosomal PD-L1 is systemically distributed and capable of suppressing T cell activity at distant sites. This review summarizes the current understanding of exosomal PD-L1 biogenesis, its immunosuppressive mechanisms, and its clinical relevance across multiple cancer types. We highlight its potential as a non-invasive biomarker for predicting therapeutic response and monitoring disease progression. Compared with tissue-based PD-L1 assessment, exosomal PD-L1 offers advantages in accessibility and dynamic reflection of tumor immune status. However, challenges remain regarding standardization of detection methods and clinical interpretation. Future directions include the integration of exosomal PD-L1 profiling into immunotherapy decision-making and the development of therapeutic strategies targeting exosome secretion. These insights may contribute to overcoming resistance in immunologically inert tumors and advancing precision oncology.